(untitled) (Jurnal Destinasi Pariwisata, 2026)
Ternate City, Highlighting the role of the home industry Pakesang as the main actor. This traditional spiced beverage not only offers a distinctive taste but also carries strong historical value rooted in the traditions of the Sultanate of North Maluku. Using a qualitative descriptive method with a 7P Marketing Mix approach and SWOT Analysis, this research seeks to formulate a sustainable development strategy. The results indicate that the implementation of the 7P strategy is quite effective in creating product differentiation. It is supported by the authenticity of flavor derived from local ingredients such as candlenuts and the utilization of diverse distribution channels, both retail and e-commerce. However, challenges remain in aspects such as depot location arrangement and packaging design, which are not yet practical for souvenir products. The current AirGuraka market is dominated by domestic tourists, with sales still highly dependent on tourism event calendars. Based on the SWOT analysis, the recommended main strategy is packaging innovation in the form of sachets or mini bottles to expand retail market reach and build partnership with local spice farmers to maintain the stability of raw material supply. Support from local government in improving depot infrastructure is also considered essential to enchance the competitiveness of AirGuraka as a culinary tourism icon of Ternate.